Contribution of Regional Tax Revenues and Retributions to Accelerate The Economic Recovery of Ambon City Post Pandemi Covid-19 - Rukmuin Wilda Payapo; Silfiena Siahainenia (Jurnal Mantik, 2022)
This study aims to analyze whether the receipt of Regional Taxes and Regional Levies is able to contribute to the acceleration of the Economic Recovery of Ambon City. This research is a qualitative research with a case and field study approach . Data collection techniques are observation and literature review. The research was conducted in Ambon City in 2020-2022. The results showed that The contribution of Ambon City Regional Tax revenue in 2020 is very good with a contribution percentage of 92.66% and in 2021 it is 92, 87% in the very good category. The trend of increasing local tax revenues shows that the regional economic recovery is gradually improving. Local governments must make breakthroughs to accelerate community economic recovery in the tourism and transportation sectors. So that it can have an impact on increasing hotel, restaurant and tourism taxes while still paying attention to health protocols. However , the contribution of regional levies in Ambon City is very less. In 2020 the contribution of regional levies to PAD decreased to 7.31% and in 2021 to 7.12%. The contribution of regional retribution is in the very poor category, triggered by the declining contribution of the Garbage/Cleaning Service Retribution to PAD in Ambon City. Indeed, the Covid-19 pandemic does not have the potential to reduce the contribution of the Garbage/Cleaning Service Retribution to Ambon City PAD. In the presence or absence of the Covid-19 Pandemic, people should still pay the garbage retribution. Because the waste generated is still there every day. The Regional Government must design a collection system that is integrated in Regional Taxes and Regional Levies, so that the management of the Waste/Cleaning Service Retribution is more transparent and accountable. As well as the supervision of everyone involved in the management of the Ambon City Waste/Cleaning Service Retribution.